COLLABORATIVE INFORMATION SYSTEM ENGINEERING AS A SUPPORTING LEARNING TOOL FOR ENGLISH FOR BUSINESS TOPIC - Dewi Selviani Yulientinah; Sari Armiati (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2011)
Learning environment in higher education can be transformed from teacher-centered environment into thecombination of learner, knowledge, and assessment-centered environment. Therefore, students learningcollaboration which can lead into competent community in line with the programs’ goals, can be created.Teacher-student interaction which is usually conducted in the classroom needs to be managed in order to buildstudents’ deep learning understanding. Based on the learning interaction among learning resources, teacherand student, an information system is enginereed. This system is an information system which functions as aCollaborative Learning (CL) supportin tool for English subject, specifically for English for Business topic.Research in CL can be viewed from seven perspectives. They are collaborative interaction control, task from CL,learning theories in collaboration, CL environment engineering, students’ roles, collaboration domain andlearning methodologies that support collaborations (Cs). Among those perspectives, CL environmentengineering becomes the basis in engineering information system which collaborates text, audio, video andpicture as an interaction tool. The specification of this interaction tool is based on the content of each lecture.The research begins by analysis phase which covers the analysis of the content of lecture and spreadingquesionnaire. The questionnaire is designed to get information on the necessity level of information system andthe description of current learning system. After the information of need specification is obtained, the phase ofinformation system engineering is conducted. In this phase, the modelling of process, data, menu structure anduser interface is created. Data modelling uses Data Flow Diagram (DFD) which consists three entities:administrator, English lecturers and students. Data modelling engineered uses Entity Relationship (ER) to relatedata entity and produces 14 tables, whereas menu structure modelling and user interface are created to showinformation system design in the implementation-phase-to-be.